Analysis of Newborn Calves Measurement for Early Selection Analysis in Aceh Bulls at The Breeding Station - Putra, WPB; Sumadi, Sumadi; Hartatik, T; Saumar, H (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2014)
Abstract. Aceh cattle is one of Indonesian germplasms with many advantages for development in the tropics. The purpose of the study was to select Aceh bulls based on newborn calves measurements. Data comprised 294 calves from nine bulls. The variance components of heritability (h2) and repeatability (r) estimation were obtained from data analysis using SPSS 16.0 software. Breeding value was estimated on the newborn calves measurement namely birth weight (BW), thoracic girth (TG), withers height (WH) and body length (BL). The genetic parameter values of newborn measurements were moderate category (0.10< h2 <0.30) for heritability (h2) and moderate (0.10<r<0.30) to high (r>0.30) for repetability (r). The average of newborn calves measurements was 13.99+1.96 kg (BW), 54.50+3.24 cm (TG), 56.37+3.41 cm (WH) and 45.13+2.86 cm (BL). Bull A (ID: P.075) was the best bull with cumulative breeding value 5.05. Key words: Aceh cattle, newborn measurements, genetic parameters, breeding value Abstrak. Sapi Aceh merupakan salah satu plasma nutfah Indonesia. Sapi ini memiliki banyak kelebihan untuk dikembangkan di daerah tropis. Tujuan penelitian ini adalah untuk menyeleksi pejantan sapi Aceh berdasarkan ukuran lahir pada pedet. Data yang digunakan terdiri dari 294 ekor pedet dari sembilan pejantan. Estimasi komponen ragam heritabilitas dan estimasi ripitabilitas dianalisis menggunakan perangkat lunak SPSS 16.0. Estimasi nilai pemuliaan dihitung berdasarkan ukuran lahir pedet: berat badan (BB), lingkar dada (LD), tinggi gumba (TG) dan panjang badan (PB). Nilai parameter genetik pada ukuran lahir termasuk kategori sedang (0,10<h2<0,30) untuk heritabilitas (h2) dan kategori sedang (0,10<r<0,30) sampai tinggi (r>0,30) untuk ripitabilitas (r). Rata-rata ukuran lahir pedet adalah 13,99+1,96 kg (BB), 54,50+3,24 cm (LD), 56,37+3,41 cm (TG) and 45,13+2,86 cm (PB). Pejantan A (ID: P.075) merupakan pejantan terbaik dengan nilai pemuliaan kumulatif sebesar 5,05. Kata kunci: Sapi Aceh, ukuran lahir, parameter genetik, nilai pemuliaan